2018
DOI: 10.1111/jopr.12781
|View full text |Cite
|
Sign up to set email alerts
|

Dental Shade Matching and Value Discernment Abilities of First‐Year Dental Students

Abstract: Females and individuals who performed better on the Farnsworth-Munsell 100 Hue Test have improved dental shade-matching ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 33 publications
4
11
0
1
Order By: Relevance
“…The gender influence on color perception is a controversial factor, with studies reporting a better performance for females 8,12‐14 or males 10,11 . However, most of the studies did not report differences between both genders 15‐20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The gender influence on color perception is a controversial factor, with studies reporting a better performance for females 8,12‐14 or males 10,11 . However, most of the studies did not report differences between both genders 15‐20 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, older observers could present an alteration in color perception 1 . The influence of gender on visual perception is controversial, some studies reported better performance for males, 10,11 others reported better performance for females 8,12‐14 . However, most of the studies did not find gender influence 15‐20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dental Color Matcher is a free online education and training program available from the Society for Color and Appearance in Dentistry 23 . The best and least expensive exercise may be the practice of matching together pairs of masked shade tabs from two exact shade guides 16,24 . Benefits of training include enhance esthetic restorative dentistry, resulting in improved patient satisfaction that will boost the patient's confidence in the provider l .…”
Section: Discussionmentioning
confidence: 99%
“…The Perceptual Ability Test (PAT) is a component of the DAT that is used to ascertain an applicant's spatial visualization skills. There is recent evidence suggesting that it may be useful in screening for the presence of CVD and the ability to match dental shades 16 . The purpose of this study was to determine if there is an association between the PAT and the presence of CVD in first‐year dental students.…”
Section: Introductionmentioning
confidence: 99%